Modulation of agronomic and nutritional response of Pleurotus eryngii strains by utilizing glycine betaine enriched cotton waste. (10th October 2019) - Khan, Asif Ali; Muhammad, Muzammil Jahangir; Muhammad, Idrees; Jan, Ibadullah; Samin, Ghufrana; Zahid, Anam; Fozia,; Muhammad, Ishaq; Wang, Peng; Lu, Lixin; Fang, Ming; Yao, Fang Jie
Abstract: BACKGROUND: This study aimed to evaluate the possibility of cotton waste enrichment with glycine betaine (GB) for production of two strains (P9, P10) of king oyster ( Pleurotus eryngii ). Cotton waste was used as (100%) control (T0 = cotton waste) and augmented with various combinations of GB, (T1 = 2 mmol L −1, T2 = 4 mmol L −1, T3 = 6 mmol L −1, T4 = 8 mmol L −1 and T5 = 10 mmol L −1 ). The response of king oyster to GB was evaluated by earliness, yield, biological efficiency (BE), minerals (nitrogen, phosphorus, potassium, zinc (Zn), copper (Cu), magnesium (Mg), manganese (Mn), iron (Fe), sodium (Na), calcium (Ca)), total sugars, total soluble solids, reducing sugars, non‐reducing sugars, ascorbic acid, proximate (crude protein, carbohydrates, crude fibers, ash, fats) content of fruiting body and Fourier‐transform infrared (FTIR) spectroscopy analysis compared with the control substrate (cotton waste). RESULTS: The earliness, yield, and BE were higher as compared to control substrate and increased with an augmentation in the concentration of GB within the cotton waste. Two strains showed (on dry weight basis) 33.9–54.9 mg g −1 nitrogen, 6.8–12.5 mg g −1 phosphorus, 16.9–25.1 mg g −1 potassium, 40.5–64.2 mg kg −1 Zn, 17.1–37.3 mg kg −1 Cu, 1174–1325 mg kg −1 Mg, 20.1–29.1 mg kg −1 Mn, 129–265 mg kg −1 Fe, 779–835 mg kg −1 Ca), 6.3%–11.3% total sugars, 7.3–14.9 °Brix total soluble solids, 2.1–7.3% reducing sugars, 10.4–18.1% crude protein, 3.6–4.4% crude fiber and 5.6–16.7 mg (100 g) ‐1 on various concentration of GB enrich cotton waste. Cotton waste enriched with GB significantly affected nutritional profile of king oyster mushroom. CONCLUSION: The results revealed that GB enriched cotton waste can be used as an innovative substrate to enhance the yield and quality of king oyster mushroom. © 2019 Society of Chemical Industry